Effect of Word Processing on Holistic Writing and Revisions by Students - Khizra; Dr. Qaisara Parveen (Journal of Peace, Development and Communication, 2024)
This study aimed to investigate how word processing affected students’ comprehensive writing and modifications. They make writing and editing easier. Word processing tools help you write better by giving you automatic help. The research was to find out the level of acquisition of skills in word processing on holistic writing and revision by students. To identify the effect of word processing on the overall quality of students’ writing in word processing on holistic writing and revision by students. This study was experimental as well as Descriptive in nature. The sample of the study was 20 students of class seventh. The sample of the research was chosen through the purposive sampling technique. Research instruments was developed by seven class students and also instrument divided by pre-test and post-test. The data was collected through per-test and post-test instrument by seven class students. The researchers were visited the target schools. Adopt rubrics design to evaluate the quality of student writing and revision. This study was a great significance in developing skills of students in word processing software. This study also contributed in the field of education, curriculum and policymaker.